Analisis Perbandingan Pengetahuan, Sikap, dan Perilaku Kesehatan Reproduksi Remaja di Kota Cirebon - Rijal Maulana; Turasih Turasih; Suryadi Suryadi (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
Awarnes of reproductive health in adolescence needs to be paid attention to considering that teenagers are vulnerable to falling into juvenile delinquency and can even become victims of sexsual violence due to a lack of knowledge about reproductive health. The government, through the Indonesian Ministry of Health, has responded to the urgency regarding knowledge of adolescent reproductive health by establishing community empowerment in the health sector through the adolescent posyandu program. Knowing the role of community empowerment in the health sector on adolescent reproductive health behavior (knowledge, attitudes, practices) is the aim of this research. Quantitative methods were used in this research and carried out in Panjunan Village, Lemahwungkuk District, Cirebon City. The subject population in the study were two groups of teenagers, namely teenagers who attended the youth posyandu and teenagers who did not attend the youth posyandu. The sample size that will be used in each group is 30 people. The hypothesis in this research is that there are differences in reproductive health behavior between teenagers who participate in youth posyandu and teenagers who do not participate in youth posyandu. Data analysis used the Mann-Whitney test statistical analysis to see differences in adolescent reproductive health behavior (knowledge, attitudes, practices). From the results of statistical analysis, it was found that there was no difference in knowledge, attitudes and practices between those attending posyandu and those not attending posyandu with a probability value greater than 0.05.